Peningkatan Proses dan Hasil Belajar Pendidikan Pancasila Menggunakan Model Discovery Learning di Kelas IV SD IT Insan Mulia Merangin - Elza April Lia; Abdulah; Elvima Nofrianni (Advances In Education Journal, 2026)
This study aimed to describe the improvement of the learning process and learning outcomes in Pancasila Education through the implementation of the Discovery Learning model among fourth-grade students at SD IT Insan Mulia Merangin. The study employed a Classroom Action Research design conducted in two cycles. Each cycle involved planning, action, observation, and reflection. The participants were 19 fourth-grade students, consisting of 10 boys and 9 girls, in the first semester of the 2025/2026 academic year. Data were collected through observation, learning achievement tests, and documentation. The achievement test consisted of 15 multiple-choice items and 5 essay questions. Data were analyzed using qualitative and quantitative descriptive techniques with a minimum mastery criterion of 68. The findings showed a consistent improvement in the learning process from Cycle I to Cycle II. Teacher implementation increased from 63% in the first meeting of Cycle I to 85% in the second meeting of Cycle II. Student learning activity increased from 37% to 79%. Classical learning mastery also improved from 63% (12 of 19 students) in Cycle I to 79% (15 of 19 students) in Cycle II. Therefore, the Discovery Learning model was effective in improving both the learning process and Pancasila Education learning outcomes of fourth-grade students at SD IT Insan Mulia Merangin.